"Religion" and "Politics": A Japanese Case. (27th May 2020) - Horii, Mitsutoshi
Abstract : Timothy Fitzgerald's The Ideology of Religious Studies should not be read as something just about "religion, " but about the modern Euro- American "secularity, " which functions to mystify the colonial matrix of power of Euro-American modernity. Fitzgerald's later work focuses on two mutually parasitic categories of "religion" and "politics." As a case study of the Fitzgeraldian perspective, this article examines the construction of the religion-politics distinction in Japan since the late nineteenth century. In the latter half of the nineteenth century the aggression of Euro-American colonial power motivated Japan's elites to institutionalize the nation based upon the Euro-American concepts of "politics" and "religion." After Japan's defeat in the Second World War in 1945, the US-led Allied Occupation redefined prewar Japanese state orthodoxy and institutions as "religion, " in order to eliminate them from the post-war Japanese statecraft.